2000
DOI: 10.1021/jf991162l
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Surfactant Headgroup Size To Alter Lipid and Antioxidant Oxidation in Oil-in-Water Emulsions

Abstract: Oxidation of oil-in-water emulsion droplets is influenced by the properties of the interfacial membrane surrounding the lipid core. To evaluate how surfactant headgroup size influences lipid oxidation rates, emulsions were prepared with polyoxyethylene 10 stearyl ether (Brij 76) or polyoxyethylene 100 stearyl ether (Brij 700), which are structurally identical except for their hydrophilic headgroups, with Brij 700 containing 10 times more polyoxyethylene groups than Brij 76. Fe(2+)-promoted decomposition of cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
4
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 12 publications
2
91
4
2
Order By: Relevance
“…Considering this finding, there is very strong relationship between the k value and the properties, especially the sizes, of the hydrophilic heads in Brij series of surfactants. Although the experimental system is different from our emulsion system, Silvestre, Chaiyasit, Brannan, McClements, and Decker (2000) reported very similar observations to our findings. In an emulsion system, the lipid oxidation rate of the emulsion acts as a stabilizing force, in surfactants with large hydrophilic heads having a lower value than surfactants with small hydrophilic heads.…”
Section: Resultssupporting
confidence: 88%
“…Considering this finding, there is very strong relationship between the k value and the properties, especially the sizes, of the hydrophilic heads in Brij series of surfactants. Although the experimental system is different from our emulsion system, Silvestre, Chaiyasit, Brannan, McClements, and Decker (2000) reported very similar observations to our findings. In an emulsion system, the lipid oxidation rate of the emulsion acts as a stabilizing force, in surfactants with large hydrophilic heads having a lower value than surfactants with small hydrophilic heads.…”
Section: Resultssupporting
confidence: 88%
“…Influence of water concentrations on reverse micelle radius in the presence of 100 mmol AOT/kg lipid, 1.0 μmol ferrous sulfate/kg lipid and 2% w/w methyl linolenate in hexadecane. Values with different letters indicate significant differences (p<0.05) 8.88 Å in no-added water system and 15.59, 15.34, 14.68, and 14.31 Å in added water system as the oleic acid concentration increased from 0, 25, 50, and 100 mmol/kg lipid, respectively. As with cumene hydroperoxide, oleic acid could act as a cosurfactant to decrease reverse micelle size because of its difference in molecular geometry.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that modification of lipid-water interfacial layers can alter lipid oxidation rates in oil-in-water emulsions. [5][6][7][8][9] Thus, it could also be possible to alter lipid oxidation in bulk oil by modifying the interfacial properties of association colloids.…”
Section: Introductionmentioning
confidence: 99%
“…Silvestre et al investigated the stability of an oil-in-water emulsion prepared with polyoxyethylene 10 stearyl ether (Brij 76) or polyoxyethylene 100 stearyl ether (Brij 700). Therefore, they implied that the interfacial thickness of an emulsion droplet could be an important determinant of the oxidative stability of an emulsion (Silvestre, 2000). Our study showed that the stability of lycopene in aqueous solution was influenced by the type and amount of emulsifier used.…”
Section: Resultsmentioning
confidence: 69%